Assyrian deeds and documents recording the transfer of property: including the so-called private contracts, legal decisions and proclamations preserved in the Kouyunjik Collections of the British Museum chiefly of the 7th Century B.C., copied, collated, arranged, abstracted, annotated, and indexed - Johns, C. H. W. (Deighton, 1898)
Vol. 1. Cuneiform texts.- Vol. 2. Additional Cuneiform texts, introduction, officials, metrology.- Vol. 3. Money loans, legal decisions, deeds of sale, slave sales.- Vol. 4. ed. by his wife, with a biographical sketch of the author, and bibliography of his published works; Sales of houses - sales of landed property - leases - votive offerings - proclamations - charters - schedules - glossary.